Membentuk Karakter Kepemimpinan Anak Usia 7-9 Tahun melalui Permainan Tradisional - Theresia Avila Clarita Oktavi; Gregorius Ari Nugrahanta (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2024)
Students who disobeyed moral rules, like brawls and corruption, reflected that they did not have leadership character. This study aims to develop a guidebook for traditional games in order to shape the leadership character of children. The research method used was Research and Development (R&D) type ADDIE, namely Analyze, Design, Develop, Implement, and Evaluate. The results of the validation of traditional game manuals had a quality of